URGENSI KELOMPOK SADAR HUKUM BAGI WANITA SINGLE PARENT; PENGALAMAN PENGABDIAN MASYARAKAT DI PESISIR SELATAN SUMATERA BARAT - Tiswarni Tiswarni (Kafa`ah: Journal of Gender Studies, 2014)
The establishing of a group that has good awareness on law for single parent women in Batu Hampa, aims at facilitating knowledge and understanding on marriage problem and resolution from law perspective, both on divorce legalization and right-obligation as a single parent. An illegal divorce will take effect of her personal and social life such as citizen status or for a remarried action. The single parent  women  were  provided  with  a  law  counseling  in  order  to prepare them as a personal that has law awareness. They were given a partner community before the counseling. Partner group supported them to establish the group which has good law awareness. In case of a family which is about to have divorce, the groups will show their care and is hoped to give the better solution. They should be able to elaborate the knowledge and are able to help the others who have the same problem.  Keywords: single parent, aware of law group, community partnersCopyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i2.99